Hubungan Kelas Diameter Terhadap Biomassa, Stok Karbon, dan Serapan CO2 pada Pohon Mahoni (Swietenia mahagoni) di Hutan Kota Bonawang Kotamobagu - Hendra Amon (Madani: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to analyze the diameter distribution and its relationship to biomass, carbon stock, and carbon sequestration in mahogany trees in the Bonawang urban forest of Kotamobagu. This is a quantitative study that employs the non-destructive sampling method, which allows data collection without permanently damaging the trees, thereby enabling the reuse of the same study subjects. Data collection techniques included both primary and secondary data. Primary data were collected through observations and measurements along a transect, where the starting point of the transect was determined using purposive sampling within a 20-meter-wide area. Secondary data were obtained from journals, books, as well as theories and the results of previous research. The results of the study indicate that the mahogany (Swietenia mahagoni) population consists of 77 individuals with diameter classes ranging from 20 cm to 160.82 cm. The largest number of mahogany individuals was found in the 30 cm to 40 cm diameter class. The total mahogany biomass was 337.98 metric tons, carbon stock was 158.77 metric tons of C, and carbon sequestration was 583.7 metric tons of CO?, with the highest values occurring in the diameter class above 100 cm. The correlations between diameter class (based on the midpoint of the diameter class) and biomass, carbon stock, and carbon sequestration in mahogany trees is very strong, with a positive correlation, and is statistically highly significant. Given that the diameter class > 100 cm (large) accounts for the largest contribution to carbon sequestration, it is recommended that area managers prioritize the protection of these trees from logging activities, as they serve as highly effective carbon sinks in mitigating climate change.